Peran Guru Pendidikan Agama Islam Dalam Membentuk Perilaku Islami Siswa Di Sekolah Menengah Kejuruan Negeri 8 Surakarta Tahun Pelajaran 2016/2017 - Hartati, Erni, Drs. Saifuddin Zuhri, M.Ag (2017)
SMKN 8 Surakarta is one of vocational schools in Surakarta in which it has competence program in arts and it becomes one of the special characteristic of the school. Sometimes, big passion of art and freedom to act have negative influences to the students' behaviour. When talking about students' behaviour and moral, it will be connected to the implementation of Islamic Education in the school environment. Based on that reason, the researcher will discuss about the roles of Islamic education teacher in forming students' islamic behaviour at SMK Negeri 8 Surakarta in academic year 2016/2017. The problems in this study as follow: 1. How is the implementation of Islamic Education at SMK Negeri 8 Surakarta in academic year 2016/2017? 2. How is the role of the Islamic Education teacher in forming students' islamic behaviour? 3. What is the obstacle faced by the teacher in forming students' islamic behaviour?. Therefore, the purpose of this study is to find and to describe out the implementation of Islamic Education in SMK Negeri 8 Surakarta, the role of the Islamic Education teacher in forming students' islamic behaviour and the obstacles. The use of this researh is give contributoin for development of konowledge, especially Islamic Education and as substance for Islamic Education teacher to forming students' islamic behavior. The research method which is used in this study is field research design with qualitative approach, using qualitative descriptive analysis and inductive of ways of thinking. The subject of this study is the chairperson, teacher of islamic education, and students of smkn 8 surakarta. The method of collecting data which is used in this study is documentation, observation, and interview. Based of the study, it can be concluded that the implementation of Islam Education in SMK Negeri 8 Surakarta is good, by using curriculum 2013 and time allotment of 3 hours for theory and habit. The roles of Islamic Education teacher in forming the students' islamic behavior is really important. There are 3 ways of forming the students' islamic behaviour; 1. Habit, by doing shalat dhuha and juma't. 2. Understanding, by giving advice and developing. 3. Model, by giving the good example for students. Meanwhile, there are 2 obstacles faced by islamic education teacher. Those are: internal factor; students' way of thinking, external factor: lack of parents' role, and influence of social media.